Cover Picture: OFF‐ON‐OFF Red‐Emitting Fluorescent Indicators for a Narrow pH Window (Chem. Eur. J. 8/2017). Issue 8 (15th December 2016) - Cidlina, Antonin; Miletin, Miroslav; Fathi‐Rasekh, Mahtab; Nemykin, Victor N.; Zimcik, Petr; Novakova, Veronika
Abstract : Two switches are shown to control the fluorescence in an efficient red‐emitting fluorescent indicator with a steep sensing profile. Intramolecular charge transfer from the peripheral tertiary amine and protonation of azomethine nitrogen atoms in azaphthalocyanine are involved in the sensing mechanism. The particular pH range is driven by the basicity of these two centers and can be simply tuned by structural changes in the molecule. More information can be found in the Full Paper by V. Nemykin, P. Zimcik, V. Novakova et al. onpage 1795 ff.